Islam Indonesia: Telaah Konstruksi Idenditas Muslim Tradisional Dan Muslim Modernis - Sutan Botung Hasibuan; Ahmad Lahmi; Dasrizal Dahlan (Indo Publishing, 2026)
This study examines the construction of traditional and modernist Muslim identities in Indonesia within contemporary social, cultural, and religious contexts. The central problem of the research concerns how historical dynamics, education, modernization, and globalization have shaped the distinctive characteristics and interactions between these two groups. The objective of this study is to identify the defining features of each group, the factors influencing shifts in religious identity, and their respective contributions to the development of Islam in Indonesia. This research employs a library-based methodology with descriptive qualitative analysis, utilizing scholarly documents, academic literature, and historical sources as primary data. The research subjects include the social representations of traditional and modernist Muslim groups in Indonesia, particularly those affiliated with pesantren networks and modernist Islamic organizations across the archipelago. The findings indicate that traditional Muslims serve as custodians of religious tradition, cultural heritage, and spiritual continuity, whereas modernist Muslims function as agents of transformation through rationality, modern education, and reinterpretation of religious texts. The interaction between these two groups generates a dialectical process that enriches the diversity of Indonesian Islam while fostering the emergence of a more moderate, adaptive, and inclusive religious expression. The study concludes that these identity constructions complement one another in strengthening the dynamic, plural, and progressive development of Islam in Indonesia.